2003
DOI: 10.1002/bit.10840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation broth and biosurfactants on mass transfer during liquid–liquid extraction

Abstract: Mass transfer rates in liquid-liquid extraction processes can be seriously affected by the presence of surface-active contaminants. This is especially true of applications of a biotechnological origin, where the microorganism used in the process may produce the surface-active contaminants. An investigation into the effects of soluble and insoluble fermentation broth components on mass transfer using chloramphenicol extraction into octanol as the model system was conducted. Soluble components produced during fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…The concentration-time data obtained from experiments are analyzed using a model based on the two-film theory to yield values for overall mass-transfer coefficients. 7 The error in determining the overall mass transfer coefficient was found to be AE4.7%.…”
Section: Extraction Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The concentration-time data obtained from experiments are analyzed using a model based on the two-film theory to yield values for overall mass-transfer coefficients. 7 The error in determining the overall mass transfer coefficient was found to be AE4.7%.…”
Section: Extraction Methodsmentioning
confidence: 93%
“…Before inoculation, all media and growth flasks were sterilized in an autoclave (Astell Hearson) at 121 C for 20 min. A previous study 7 had determined the effect of the media and fermentation broth components on mass transfer.…”
Section: Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method was also tested with surfactin synthesized from culture broth of B. subtilis ATCC 21332. This fermentation broth also contained other fermentation products and residues such as proteins, sugar, lipid compounds and different types of amino acids (Pursell et al 2004). The complex nature of B. subtilis ATCC 21332 culture broth makes identification and quantification of surfactin difficult.…”
Section: Sensitivitymentioning
confidence: 99%
“…An extraction system involving the recovery of phenylalanine by the quaternary ammonium compound Aliquat 336 has been studied previously by a number of researchers (Haensel et al, 1986;Pursell, 2001;Scarpello and Stuckey, 2000;Uddin et al, 1990Uddin et al, , 1992. It has been shown that Aliquat 336 is an effective extractant for phenylalanine, with recovery yields of up to 95% being reported (Scarpello and Stuckey, 2000).…”
Section: Introductionmentioning
confidence: 99%